Material Parameter Identification and Inverse Problems in Soft Tissue Biomechanics - Avril, Stéphane; Evans, Sam (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2017)
The articles in this book review hybrid experimental-computational methods applied to soft tissues which have been developed by worldwide specialists in the field. People developing computational models of soft tissues and organs will find solutions for calibrating the material parameters of their models; people performing tests on soft tissues will learn what to extract from the data and how to use these data for their models and people worried about the complexity of the biomechanical behavior of soft tissues will find relevant approaches to address this complexity.